2020
DOI: 10.3390/antiox9111122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rutin on Wound Healing in Hyperglycemic Rats

Abstract: Long-term poor glycemic control negatively affects macrovascular and microvascular diseases, as well as wound restoration. Buckwheat is a good source of rutin (quercetin-3-O-rutoside) and has benefits in regulating blood sugar. This study was to evaluate the antioxidant and anti-inflammatory effects of rutin on wound healing in streptozotocin-induced hyperglycemic rats. Eighteen male Wistar rats were randomly divided into three groups: normal (NDM), hyperglycemic (DM), and hyperglycemic with rutin (DMR). After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…Numerous compounds such as flavonoids, organic acids, iridoids, triterpenoids and volatile components have been reported from this plant ( Song et al, 2014 ). Rutin is a flavonoids compound and has been proved antioxidant and anti-inflammatory effects through promoting production of antioxidant enzyme and reducing the expression of proinflammatory cytokine such as NF-κB ( Chen et al, 2020 ). CGA is an organic acids compound and as a quality control index component of Jin Yin Hua.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous compounds such as flavonoids, organic acids, iridoids, triterpenoids and volatile components have been reported from this plant ( Song et al, 2014 ). Rutin is a flavonoids compound and has been proved antioxidant and anti-inflammatory effects through promoting production of antioxidant enzyme and reducing the expression of proinflammatory cytokine such as NF-κB ( Chen et al, 2020 ). CGA is an organic acids compound and as a quality control index component of Jin Yin Hua.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vivo model of tissue regeneration, the administration of rutin-supplemented hydrogels reduced the wound area in rats, attributed to a decrease in oxidative stress markers (e.g., lipid peroxidation); the production of carbonyl protein through the oxidation of certain amino-acids, including lysine, proline, or arginine; and/or a treatment-induced increase in protein levels [ 26 ]. In another rat study, the intraperitoneal administration of rutin proved effective in the treatment of diabetic ulcers, reducing the wound area and increasing the percentage closure by stimulating the production of antioxidant enzymes and inhibiting the expression of metalloproteinases and vascular endothelial growth factor (VEGF), thereby lowering oxidative stress and inflammatory responses [ 27 ]. In an in vitro study, Pivec et al [ 28 ] demonstrated that the water-based enzymatic polymerization of rutin enhances its antioxidant activity, promoting the viability of fibroblasts and HaCat cells (non-tumoral human keratinocytes), evidencing its potential usefulness in tissue regeneration and wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…Through HPLC analysis, rutin (a flavonol glycoside) was found to be one of the major flavonoids in CPFD and CPEE, in accordance with the literature [ 20 , 43 ]. Rutin is well known for its wound-healing and antioxidant properties, which may partly explain the reason why CPFD and CPEE enhanced fibroblast proliferation after post-treatment with H 2 O 2 [ 44 , 45 ]. Rutin has been proven to enhance the production and accumulation of extracellular matrices during the fibroblast healing process [ 44 ].…”
Section: Discussionmentioning
confidence: 99%